PEMAKNAAN VESPA EXTREME BAGI PENGGUNA VESPA EXTREME DI KOTA PEKNBARU DALAM PERSEKTIF FENOMENOLOGI - Deri Ibrahim; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Vespa extreme is a symbol of freedom in modification and creation art which combined things that useless with vespaso that become anunique phenomena. This vespa extreme rider known because their appearance look dingy, seedy, and their unique life style. This appearance make people afraid and have a negative perspective to them. This research purpose to know motive of vespa extreme user included meaning of vespa, symbols and so things in vespa extreme and about its rider communication experience in use vespa extreme.This research is using qualitative with phenomenology approach by Alfred Schutz and interaction symbolic theory George . H. Mead. This research have 7 people as informant. Sampling technique using snowball technique.Data collection with participant observation, documentation, and deep interview. Data analysis is interactive technique included 3 phase, data collection, data interpretation, and conclucion.The results showing that motive of vespa extreme riders join this community is the past motive like modification hobby and using scooter that have been long exist in their self, element of art, unique and space of freedom in creation. And future motive include solidarity, looking for friends and expand brotherhood as media for freedom in creation. The meaning of vespa extreme for its user is media to express their self freely, self identity, and vespa extreme as media communication to deliver message and satire. Besides, the meaning of things in that like flag and plastic is use as sign in the road. Bottles,spare tire, and many more for additional tools is the variation modification. Communication experience that they gained is expand brotherhood, become famous, and also some not fun experience like thought as criminal, homeless, useless, get caught by the police, be treated unreasonable, and often gets shout also thrown by other pedestrians.